A mechanism for the multidecadal modulation of ENSO teleconnection with Europe. - López Parages, Jorge; Rodríguez-Fonseca, Belén; Terray, Laurent (Springer, 2014)
El Niño phenomenon is the main oceanic driver of the interannual atmospheric variability and a determi- nant source of predictability in the tropics and extratrop- ics. Several studies have found a consistent and statisti- cally significant impact of El Niño over the North Atlantic European Sector, which could lead to an improvement of the skill of current seasonal forecast systems over Europe. Nevertheless, this signal seems to be non-stationary in time and it could be modulated by the ocean at very low fre- quencies. Hence, the seasonal climate predictability based on El Niño could be variable and only effective for spe- cific time periods. This study considers the multidecadal changes in the ocean mean state as a possible modulator of ENSO-European rainfall teleconnection at interannual timescales. A long control simulation of the CNRM-CM5 model is used to substantiate this hypothesis and to assess if it can be relevant to explain the non-stationary behavior seen in the twentieth century. The model reproduces the leading rainfall mode over the Euro-Mediterranean region, and its non stationary link with El Niño. This teleconnec- tion has been identified in coincidence with changes of the zonal mean flow at upper levels, which influence the propagation of the waves from the tropics to extratropics through the atmosphere and, hence, to explain the changing impact over Europe. However, the non-stationary impact observed along the twentieth century could also be related to the observed changes in the interannual oceanic forcing signal itself. The results obtained suggest, for both hypoth- eses, an important role of the natural internal variability of the ocean at multidecadal timescales.
https://v2.sherpa.ac.uk/id/publication/7889
Keywords: Meteorología; Precipitaciones atmosféricas - Europa; Atmospheric teleconnection; ENSO; European rainfall; Multidecadal modulation